Skin epidermal keratinocyte p53 induces food uptake upon UV exposure - Parikh, Shivang; Parikh, Roma; Harari, Marco; Weller, Aron; Bikovski, Lior; Levy, Carmit (Frontiers in Behavioral Neuroscience, 2023)
The first cells affected by UVB exposure are epidermal keratinocytes, and p53, the genome guardian, is activated in these cells when skin is exposed to UVB. UVB exposure induces appetite, but it remains unclear whether p53 in epidermal keratinocytes plays a role in this appetite stimulation. Here we found that food intake was increased following chronic daily UVB exposure in a manner that depends on p53 expression in epidermal keratinocytes. p53 conditional knockout in epidermal keratinocytes reduced food intake in mice upon UVB exposure. To investigate the effects of p53 activation following UVB exposure, mice behavior was assessed using the staircase, open-field, elevated-plus maze, and conditioned-place preference tests. In addition to effects on appetite, loss of p53 resulted in anxiety-related behaviors with no effect on activity level. Since skin p53 induces production of β-endorphin, our data suggest that UVB-mediated activation of p53 results in an increase in β-endorphin levels which in turn influences appetite. Our study positions UVB as a central environmental factor in systemic behavior and has implications for the treatment of eating and anxiety-related disorders.